A comparison of techniques for size measurement of nanoparticles in cell culture medium. Issue 26 (21st June 2016) - Gollwitzer, Christian; Bartczak, Dorota; Goenaga-Infante, Heidi; Kestens, Vikram; Krumrey, Michael; Minelli, Caterina; Pálmai, Marcell; Ramaye, Yannic; Roebben, Gert; Sikora, Aneta; Varga, Zoltán
Abstract : Four common size analysis techniques were applied to engineered silica nanoparticles suspended in purified water, in physiological buffer and in cell culture medium, and the results were compared using uncertainty estimates. Abstract : Plain and aminated silica nanoparticles dispersed in purified water, in 50 mM Tris–HCl buffer and in cell culture medium were measured using dynamic light scattering (DLS), centrifugal liquid sedimentation (CLS), small-angle X-ray scattering (SAXS), and particle tracking analysis (PTA). The test samples were measured by all methods immediately after dispersion and after incubation at room temperature for 24 h. The effect of the biological dispersion medium on the modal value of the particle size distribution was compared for each method taking into account the estimated uncertainty. For the methods based on light scattering, DLS and PTA, the size distributions obtained were significantly altered due to the formation of a protein corona and induced agglomeration effects. With SAXS and CLS, the measured size of the primary particles was mostly unchanged. While SAXS offers excellent precision and traceability to the SI unit system if the model fitting approach is used for data analysis, CLS provides detailed size distributions from which additional information on the agglomeration state can be deduced.